Service Quality and Client Satisfaction in Public Sector: An Empirical Assessment of the Philippine Social Security System Using the SERVQUAL Framework - Acuña, Vincent; Cerado, Ernie (JPAIR Multidisciplinary Research, 2026)
Client satisfaction is regarded as major indicator of service excellence in government institutions. This study assessed the quality of services delivered by the Social Security System (SSS) personnel in Southern Mindanao and examined its influence on client satisfaction using the SERVQUAL framework. Particularly, it aimed to determine the level of service quality across five dimensions, namely: tangibility, reliability, responsiveness, assurance, and empathy, evaluate the extent of client satisfaction, test the relationship between the two variables, and examine potential differences across branches. A descriptive-correlational research design was employed, involving 89 SSS personnel and 1,014 walk-in clients selected through proportionate stratified random sampling. Validated instruments like the SERVQUAL-based questionnaire and the official Client Satisfaction Survey of SSS, were utilized for data gathering. Descriptive statistics, regression analysis, and Kruskal-Wallis tests guided the data analysis. Results showed a consistently very high level of perceived service quality and client satisfaction in all dimensions. Assurance, tangibility, and empathy surfaced as vital strengths in service delivery. Statistical analysis proved a strong and significant positive relationship between service quality and client satisfaction, with reliability, assurance, and empathy as the most influential predictors. No significant differences were noted across branches or personnel sections, indicative of institutional coherence and consistency in service standards. These findings attest the effectiveness of SSS in providing citizen-focused public service and emphasize the need for continuous innovation, staff development, and responsive governance to sustain and enhance client-centered performance.
Keywords: Social Science; Client Satisfaction; Service Quality; Social Security System (SSS); SERVQUAL Framework; Client-centered Performance; Philippines